(untitled) (Marketing Journal, 2026)
Abstract The article analyzed the role of the compliance control system in preventing financial crimes in commercial banks. The study examined internal control mechanisms, monitoring processes based on AML/CFT requirements, and the implementation of a risk-based approach. The institutional status of compliance units, their level of independence, and integration with digital technologies were assessed. The effectiveness of KYC procedures and automated analytical tools in detecting suspicious transactions was demonstrated. The findings confirmed that strengthening the compliance function at the strategic level contributes to reducing financial risks. Based on the results, practical recommendations for improving the system were developed. Keywords: compliance control, financial crimes, banking system, AML/CFT, internal control